Luba folklore and women's ethno-gendered discourse of wifehood in “Cintu Wa Bujitu” - Mulamba, Nshindi-Germain (Afrika Focus, 2013)
This paper investigates Lubà-kasààyi folklore, particularly a folk song, in order to reveal an ethno-gendered construction of wifehood. It aims to show girls’ socialization into a sexist and patriarchal discourse and how such a practice ideologically initiates them into their future subservient role of caterers for the husbands’ alimentation needs. Moreover, folklore seems to perpetuate traditions, and so the gender inequality inscribed within them, a situation that is particularly apparent in villages. Key words: anthropological linguistics, ethno-gendered discourse, Lubà folklore, folk song, wifehood